Diterpene glycosides, acetophenone glycosides and tannins from polar extracts of the root of Euphorbia fischeriana with cytotoxicity and antibacterial activities. (November 2022) - Du, Kaicheng; Zhang, Zhiqi; Jing, Di; Wang, Yumeng; Li, Xingyao; Meng, Dali
Abstract: The phytochemical study on Euphorbia fischeriana, a folk medicinal plant in China, led to the isolation of eight undescribed glycosides, including two diterpene glycosides, three acetophenone glycosides and three tannins together with eight known ones. Their planar structures were elucidated by extensive analyses of 1D, 2D NMR experiments and HRESIMS. The absolute configurations were determined by NOESY experiments, ECD calculations. All undescribed compounds were evaluated for their cytotoxicity and antibacterial activities in vitro . Two diterpene glycosides (1–2) showed cytotoxic activity with IC50 values ranging from 5.4 to 16.2 μM toward Hep-G2, Hep-3B, A549, NCI–H460 and AGS cells. Tannins (6–8) showed the significant antibacterial activity with MIC values in the range of 1.56–6.25 μg/mL. Graphical abstract: Image 1 Highlights: Eight undescribed glycosides were isolated from the Euphorbia fischeriana . The absolute configuration of 1 and 2 was determined by ECD calculation. Cytotoxicity and antibacterial activity of compounds 1–8 was tested in vitro .